Impacted cisterna magna without syringomyelia associated with spastic paraparesis: case report - Gonçalves da Silva José Alberto; Costa Maria do Desterro Leiros da; Holanda Maurus Marques de Almeida; Melo Luiz Ricardo Santiago; Araújo Antônio Fernandes Almeida de; Viana André Pachelli Bezerra (Arquivos de Neuro-Psiquiatria)
We report on a 49 year old man with impacted cisterna magna without the presence of syringohydromyelie (SM). The clinical picture was characterized by spastic paraparesis. Magnetic resonance imaging depicted a cisterna magna filled by the cerebellar tonsils. Six months after osteodural-neural decompression of the posterior fossa there was resolution of neurological symptoms and signs with the exception of hyperactive patellar and Achilles reflexes.